ANALISIS KEMAMPUAN KOMUNIKASI SISWA SMP KELAS VII DALAM MENYELESAIKAN SOAL ARITMATIKA SOSIAL - Hasina, Anisa Nurul; Rohaeti, Euis Eti; Maya, Rippi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study aims to analyze the mathematical communication skills of Grade VII students in solving social arithmetic problems. The method in this study is a descriptive qualitative method, the subject consists of 32 students of class VII D one of the State Junior High Schools in West Bandung Regency. The stages in this research are stage 1). Preparation, 2). Implementation and 3). Evaluation, the instrument used was a test instrument that had been validated with social arithmetic material. The data collection technique of this study was the result of the instrument. The results showed that students' mathematical communication skills were still low.